UJI FITOKIMIA DAN PENENTUAN AKTIVITAS ANTIOKSIDAN DARI MADU Trigona incisa - Gunawan, Rio; -, Erwin; -, Syafrizal (Jurusan Kimia FMIPA UNMUL, 2018)
Trigona Incisa honey is flower nectar and pollen are known to have properties that are very good for health used as ingredients or cosmetic. This study aims to determine the content of secondary metabolites and determination of antioxidant activity of honey Trigona incisa which is a natural product that is found. Do fractionation using ethanol, n-hexane and ethyl acetate determination of the content of secondary metabolites was conducted using harbone and antioxidant activity was determined by testing against DPPH free radicals by measuring the absorbance of DPPH (diphenyl -1- using 2,2- picrylhidrazyl) at a wavelength of 517 nm. Phytochemical test results to the fraction of ethanol, ethyl acetate and n-hexane of Honey Trigona incisa. Showed that the alkaloid compounds, Triterpenoid and Flavonoids present in fractions of ethanol and ethyl acetate fraction. Alkaloid contained in n-hexane fraction. The results showed the ethanol and ethyl acetate fractions thought to contain flavonoid, while the antioxidant activity of the ethyl acetate fraction larger than the fraction of n-hexane and ethanol role in this case amounted to 97.00 ppm, 249 ppm and 233.85 ppm. This shows that the ethyl acetate fraction contains more antioxidant components.